(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The architecture and spatial form of the Old City of Waingapu are the result of the development of Manangamesi Harbor, which occurs between the city space and the environmental elements behind it so that an overview of its problems can be obtained to date. This research aims to provide suggestions for factors that can be integrated from the Manangamesi area using qualitative descriptive methodology. The analysis used is Urban network analysis by approaching the location or object being studied. The research results indicate that the Manangamesi area originated from the estuary’s geographical location as a fishing anchorage and the barter trade between inland tribes and coastal residents in the pre-Swampaja era. During the Swapraja era, this trade became the foundation for the Manangamesi area’s development. During the colonial era, the Manangamesi area began to flourish. Current population, economic, and ecological growth are causing a decline in regional quality in the Manangamesi area. Examining regional ecology, architecture, and design, this study addresses the shortcomings of earlier research on the Manangamesi region and is superior to other interdisciplinary sciences that concentrate on science, environmental studies, and more economic research. Recommendations for additional multidisciplinary research in the fields of architecture, urban planning, ecology, economics, tourism, and politics are necessary for the development of the Manangamesi area.